Hubungan Pengetahuan dan Paritas terhadap Waktu Penyembuhan Luka Jahitan Perineum pada Masa Nifas - Heni Sudarmini; Suprida Suprida; Merisa Riski; Turiyani Turiyani (Universitas Batanghari Jambi, 2022)
Perineal rupture is an injury to the perineum caused by natural tissue damage due to the pressure of the fetal head or shoulder during the delivery process. The purpose of the study was to determine the relationship between maternal knowledge and parity on the healing time of perineal sutures during the puerperium in the independent practice of midwife Rusmawati Gasing, Banyuasin Regency in 2021. The method used in this study was an analytical survey with a cross sectional approach. The statistical test used is the chi-square test. The sample of this study was 30 respondents who were taken by accidental sampling technique. Data obtained from the results of univariate and bivariate analysis. Based on the results of bivariate analysis with Chi square statistical test = 0.05. In the knowledge variable value 0.030 < = 0.05, this means that there is a significant relationship between knowledge and the healing time of perineal sutures during the puerperium. In the parity variable value 0.013 < = 0.05, this means that there is a significant relationship between parity and the healing time of perineal sutures during the puerperium. The results of this study are expected to be used as input, a source of information to be used in accelerating the healing time of perineal sutures in postpartum mothers so that infection is avoided.